2022
DOI: 10.3389/fneur.2022.796933
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D as a Risk Factor for Multiple Sclerosis: Immunoregulatory or Neuroprotective?

Abstract: Vitamin D insufficiency during childhood has been linked to the development of multiple sclerosis (MS), typically an adult-onset inflammatory demyelinating disease of the central nervous system (CNS). Since vitamin D was known to have immunoregulatory properties on both innate and adaptive immunity, it was hypothesized that low vitamin D resulted in aberrant immune responses and the development of MS. However, vitamin D receptors are present on many cell types, including neurons, oligodendrocytes, astrocytes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 228 publications
(201 reference statements)
0
15
0
2
Order By: Relevance
“…In another study, a dose of 1000 μg/d oral cholecalciferol syrup significantly increased VDR mRNA expression in asthmatic Egyptian children (n 29) (40) . In addition, regular intake of vitamin D supplements among the asthmatic patients increased the serum 25OHD followed by a decrease of VDR mRNA expression (40,41) which was also observed in cancer (42) and multiple sclerosis patients (43,44) . The plausible reason for the increase in 25OHD followed by a reduced VDR expression could be that 25OHD arbitrates the binding of VDR-retinoid X receptor to the promoter sequence of CYP24A1 gene that degrades 25OHD as a negative feedback mechanism (45) .…”
Section: Time and Dose-dependent Variation On Vitamin D Supplementati...mentioning
confidence: 72%
See 1 more Smart Citation
“…In another study, a dose of 1000 μg/d oral cholecalciferol syrup significantly increased VDR mRNA expression in asthmatic Egyptian children (n 29) (40) . In addition, regular intake of vitamin D supplements among the asthmatic patients increased the serum 25OHD followed by a decrease of VDR mRNA expression (40,41) which was also observed in cancer (42) and multiple sclerosis patients (43,44) . The plausible reason for the increase in 25OHD followed by a reduced VDR expression could be that 25OHD arbitrates the binding of VDR-retinoid X receptor to the promoter sequence of CYP24A1 gene that degrades 25OHD as a negative feedback mechanism (45) .…”
Section: Time and Dose-dependent Variation On Vitamin D Supplementati...mentioning
confidence: 72%
“…Same dose on relapsing and remitting multiple sclerosis patients (n 31) (34) significantly upregulated TGF-β2 mRNA expression in the PBMC similar to those reported in other studies (54)(55)(56) . Yet, some studies reported no significant effect of vitamin D supplementation in multiple sclerosis patients (44,45,(57)(58)(59) showing mixed results.…”
Section: Time and Dose-dependent Variation On Vitamin D Supplementati...mentioning
confidence: 99%
“…The role of vitamin D insufficiency, mainly in childhood, is heavily studied as a risk factor for developing multiple sclerosis (MS). 2 Several mechanisms have been proposed, including the interaction with other risk factors, such as Epstein Barr Virus (EBV) infection. 2 , 3 In contrast, the role of vitamin D in MS progression and relapses is controversial.…”
Section: Dear Editormentioning
confidence: 99%
“… 2 Several mechanisms have been proposed, including the interaction with other risk factors, such as Epstein Barr Virus (EBV) infection. 2 , 3 In contrast, the role of vitamin D in MS progression and relapses is controversial. Several studies have failed to show favorable effects of vitamin D supplementation on MS progression or relapse reduction while others suggested a possible inverse association with MS disability.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation